PENGARUH LITERASI KEUANGAN, KONTROL DIRI, DAN PENGGUNAAN E-MONEY TERHADAP PERILAKU KONSUMTIF PEKERJA PRODUKSI PT PERTAMINA BALIKPAPAN - Hermin Nainggolan (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
This study aims to determine the effect of financial literacy, self control, and e-money usage on consumptive behavior of PT Pertamina Balikpapan production workers. Consumptive behavior (Y) is the dependent variable while financial literacy (X1), self control (X2), and e-money usage (X3) are independent variables. The results of the classical assumption test state that this study is free from multicollinearity, autocorrelation, heteroscedasticity, and is normally distributed. The results of multiple linear regression obtained the results Y = 14,883 - 0,354X1 - 0,173X2 + 0,303X3 + e. The results of hypothesis testing with the f test show the results of f count (26,139) > f table (2,67) and the significance level is 0,000 < 0.05, so the first hypothesis is accepted. While the results of the t test show that partially financial literacy is the most dominant independent variable with the results of -t count (-4,454) < -t table (-1,9785) and the significance level is 0,00 < 0,05 so the second hypothesis is accepted. The coefficient of determination showed R2 = 0.364, which means contribution of independent variables 36.4%, while the remaining 63.6% is explained by other variation that is not examined in this study.